Struktur dan Sistem Sosial pada Aras Wacana dan Praksis - Kusmanto, Thohir Yuli; Elizabeth, Misbah Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2018)
The social phenomenon that became the focus of sociology has diversity in the aspects of social life of society both as a real and practical reality as well as abstract and utopian reality. The reality is static and moves dynamically inherent in social processes in the daily life of social setting. The social process shapes reality as part of the past takes place today and becomes a hope for the future. Among the social phenomena that become part of the fundamental study of sociology are structure and social system. Social structure is a process of social interaction that lasts a long time, regularly and form a pattern. The social system is a functional social interaction of a set of elements in a group or society to defend the boundaries or unity of its parts. Both in this context are interesting to explain the process of its formation, relationships, functions, traits and changes in discourse and praxis. Applying literature study this article will explore the processes of formation, relationships, functions, traits, and changes of social structure and social system in discourse and praxis. The effort is important to strengthen the sociology repertoire on the macro and abstract level.